2009
DOI: 10.1186/ar2842
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between disease activity, sleep, psychiatric distress and pain sensitivity in rheumatoid arthritis: a cross-sectional study

Abstract: IntroductionDespite recent advances in anti-inflammatory therapy, rheumatoid arthritis (RA) patients continue to rate pain as a priority. The etiology of RA pain is likely multifactorial, including both inflammatory and non-inflammatory components. In this study, we examine the association between disease activity, sleep, psychiatric distress and pain sensitivity in RA.MethodsFifty-nine female RA patients completed questionnaires and underwent pressure pain threshold testing to assess hyperalgesia/allodynia at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
2
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 46 publications
8
98
2
5
Order By: Relevance
“…In a survey on the relationship between RA activity, sleep, psychiatric distress and pain sensitivity indicated no significant relation between pains with QOL but the sleep disorders had direct and significant relation with pain. 16 In this study we observed significant difference between QOL with various aspects of sleep. Our findings indicated that there were significant relations between apnea, twitch leg during sleep, numbness of legs with the QOL.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In a survey on the relationship between RA activity, sleep, psychiatric distress and pain sensitivity indicated no significant relation between pains with QOL but the sleep disorders had direct and significant relation with pain. 16 In this study we observed significant difference between QOL with various aspects of sleep. Our findings indicated that there were significant relations between apnea, twitch leg during sleep, numbness of legs with the QOL.…”
Section: Discussionmentioning
confidence: 51%
“…12 Moreover, some disturbances during sleep cause cardiovascular diseases, 13 behavioral disturbances, depression 14 and anxiety. 15 Reduction of general health, pain and negative effects on quality of life are common in RA, 16 however fewer researches have been done on sleep disorders of patients with RA. Although new methods for RA have been presented with new medical technology, but there have not been significant outcomes in solving the psychosocial and sleep problems of these patients.…”
mentioning
confidence: 99%
“…It has been suggested previously that the development of generalized and widespread pain in RA may be in large part related to the inflammatory impact on the peripheral nerves 21. Thus, inflammatory actions on nerve endings, including nociceptive fibers, may result in long‐term sensitization, which contributes to chronic pain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, augmented central pain processing is associated with more severe pain, and normalization of central pain processing accompanies pain relief after arthroplasty (5,6). However, in inflammatory arthritis models central sensitization develops alongside synovitis (7), and widespread reduced pressure pain thresholds are associated with inflammatory disease activity in rheumatoid arthritis (RA) (8,9). Central sensitization might therefore be mediated by inflammation, rather than its accompanying pain, and widespread augmentation of central pain processing might be driven by circulating factors such as cytokines (10) rather than directly by nociceptive drive.…”
Section: David a Walshmentioning
confidence: 99%